MOF negatively regulates estrogen receptor α signaling via CUL4B-mediated protein degradation in breast cancer - Zhang, Xu; Yang, Yang; Li, Danyang; Wu, Zhen; Liu, Haoyu; Zhao, Ziyan; Zhu, Hongying; Xie, Fei; Li, Xiangzhi (Frontiers in Oncology, 2022)
Estrogen receptor α (ERα) is the dominant tumorigenesis driver in breast cancer (BC) and ERα-positive tumors (ERα+ BC) accounts for more than two-thirds of BC cases. Mof (males absent on the first), is a highly conserved histone acetyltransferase that acetylates lysine 16 of histone H4 (H4K16) and several non-histone proteins. Unbalanced expression of MOF has been identified and high MOF expression predicted a favorable prognosis in BC. However, the association of MOF with ERα and the regulatory mechanisms of MOF in ERα signaling remain elusive. Our study revealed that the expression of MOF is negatively correlated with that of ERα in BC. In ERα positive BC cells, MOF overexpression downregulated the protein abundance of ERα in both cytoplasm and nucleus, thus attenuating ERα-mediated transactivation as well as cellular proliferation and in vivo tumorigenicity of BC cells. MOF promoted ERα protein degradation through CUL4B-mediated ubiquitin–proteasome pathway and induced HSP90 hyperacetylation that led to the loss of chaperone protection of HSP90 to ERα. We also revealed that suppression of MOF restored ERα expression and increased the sensitivity of ERα-negative BC cells to tamoxifen treatment. These results provides a new insight into the tumor-suppressive role of MOF in BC via negatively regulating ERα action, suggesting that MOF might be a potential therapeutic target for breast cancer.